Universities as anchor institutions: Integrating the element of trust for developing transformational community university partnerships: - Hornby, Diana; Maistry, Savathrie Margie (Critical Studies in Teaching and Learning, 2025)
The deep and entrenched inequality existing in Makhanda is a microcosm of South Africa. The relationship between the community of Makhanda and Rhodes University is interdependent and interconnected. Community engagement has the potential to mitigate the past image of universities as institutions disconnected from the realities of the local context. However, trust becomes an imperative first step towards unravelling the local radical entanglement and for enacting transformative collaborative partnerships between community and university. This paper is based on a qualitative study which examines the conceptualization of an anchor university for the South African context through community engagement using Rhodes University as a case study. The study proposes that the element of trust is imperative to establish transformational community-university partnerships that supports anchoring Rhodes University in Makhanda. The findings reveal community engagement’s role in anchoring the university and the extent to which the element of trust pervades the relationship between the two systems to unravel radical entanglements of the past that impede holistic development.